MEMBACA GERAKAN POLITIK NAHDLATUL ULAMA DALAM PARTAI MASYUMI - Nilma Yola (Universitas Islam Negeri Imam Bonjol Padang, 2013)
This article is intended to read the pattern of political movement of Nahdlatul Ulama (NU) in Masjumi,starting from the beginning of establishment until the breakaway. In the beginning of the party’s establishment,NU is as one of the organizations that are not only participate pioneered, but also keen to gain support. In thestructure of management, NU also gained a strategic position, namely as chairman of the Majelis Shura whichwas held by KH Wahid Hasyim. Several years escorting Masjumi, NU finally decided to come out. Among theclaims raised was that NU did not get the position as minister of religious affairs in the cabinet. This claimtended to consider that NU was pragmatic. Further explored, the issue of ministerial posts just as triggers.Fundamental problems that caused this mass secession is a political movement patterns that are inconsistentamong people NU with others. In fact, with a strategic position as chairman of the the shura council, coupledwith the support of the nahdhiyin large enough then, NU may take more of a role, be more dominant, and evenchanged the course of the party. However, NU chose to get out of Masjumi. For this reason, it is important tounderstand the characteristics and patterns of NU's political movement, especially in relation to the dynamicsof Masjumi’s Party.